2020
DOI: 10.21037/jtd-20-689
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound-guided erector spinae plane block for postoperative management of video-assisted thoracoscopic surgery: a prospective, randomized, controlled clinical trial

Abstract: Background: Video-assisted thoracoscopic surgery (VATS) is a commonly performed minimally invasive procedure that has led to lower levels of pain, as well as procedure-related mortality and morbidity. However, VATS requires analgesia that blocks both visceral and somatic nerve fibers for more effective pain control. This randomized controlled trial evaluated the effect of erector spinae plane block (ESPB) in the postoperative analgesia management of patients undergoing VATS. Methods: We performed a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
0
36
1
Order By: Relevance
“…VATS is a commonly performed minimally invasive procedure that has helped to reduce levels of pain, but pain remains an issue associated with VATS, especially for the first 3 days after surgery, and it requires analgesia that blocks both visceral and somatic nerve fibres for more effective pain control so as to improve postoperative outcome. 36–38 It has been reported that regional techniques combined with general anaesthesia provide better perioperative analgesia by completing the somatosensorial and sympathetic block and have an opioid analgesic sparing effect. 39 The results of our study suggest that the average NRS score within 48 h postoperatively in group TG was significantly lower than that in group GA ( P <0.05), which is consistent with the results of Qiu et al 40 who found that TPVB provided analgesia that was superior to general anaesthesia alone during the initial 2 h after VATS in a noninferiority randomized trial.…”
Section: Discussionmentioning
confidence: 99%
“…VATS is a commonly performed minimally invasive procedure that has helped to reduce levels of pain, but pain remains an issue associated with VATS, especially for the first 3 days after surgery, and it requires analgesia that blocks both visceral and somatic nerve fibres for more effective pain control so as to improve postoperative outcome. 36–38 It has been reported that regional techniques combined with general anaesthesia provide better perioperative analgesia by completing the somatosensorial and sympathetic block and have an opioid analgesic sparing effect. 39 The results of our study suggest that the average NRS score within 48 h postoperatively in group TG was significantly lower than that in group GA ( P <0.05), which is consistent with the results of Qiu et al 40 who found that TPVB provided analgesia that was superior to general anaesthesia alone during the initial 2 h after VATS in a noninferiority randomized trial.…”
Section: Discussionmentioning
confidence: 99%
“…14 Post-thoracotomy pain syndrome is a common experience for patients undergoing thoracic surgery and has debilitating consequences associated with inadequate analgesic efficacy. 15 Despite the advantages of the minimally invasive surgical technique, video-assisted thoracoscopic surgery (VATS) with mini-thoracotomy is painful with stimulation of both visceral and somatic nociceptive nerve fibres. 15 The ESP block at the level of the fifth thoracic vertebra (T5) in patients undergoing mini-thoracotomy was evaluated for postoperative analgesic efficacy.…”
Section: Cardiothoracicmentioning
confidence: 99%
“…15 Despite the advantages of the minimally invasive surgical technique, video-assisted thoracoscopic surgery (VATS) with mini-thoracotomy is painful with stimulation of both visceral and somatic nociceptive nerve fibres. 15 The ESP block at the level of the fifth thoracic vertebra (T5) in patients undergoing mini-thoracotomy was evaluated for postoperative analgesic efficacy. 15,16 Reports have shown that patients undergoing a minithoracotomy who receive ESP blocks have lower postoperative pain scores compared to both those who receive intercostal nerve blocks (p < 0.05) 16 and those who receive no regional block (p = 0.005), 15 respectively.…”
Section: Cardiothoracicmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, ten studies [12,15,17,18,20,22,[24][25][26][27] and five studies [12,15,[25][26][27] reported postoperative 12 hour pain scores at rest or movement respectively. Pain scores of the ESPB group were significantly lower than those of the control group at rest or movement.…”
Section: Postoperative 12 Hour Pain Scoresmentioning
confidence: 99%